Silymarin, the antioxidant component of silybum marianum, protects against oxidative organ injury in a rat model of sepsis - (:unkn) unknown (My University, 2006)
[No abstract available]
Keywords: Brain; Lung; Oxidative injury; Sepsis; Silymarin